2017
DOI: 10.1177/000313481708300825
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Clostridium difficile Infection after Diverting Loop Ileostomy and Colonic Lavage: An Unreported Complication of the Novel Surgical Therapy

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, Neal et al reported only one case of CDI recurrence (2%) which was treated successfully with repeated lavage through the ileostomy. In contrast, Fashandi et al 13 reported CDI recurrence in 40% (n = 4) of the DLI group which occurred 1-7 months after surgery. All cases were successfully treated with vancomycin per ostomy or fecal transplant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, Neal et al reported only one case of CDI recurrence (2%) which was treated successfully with repeated lavage through the ileostomy. In contrast, Fashandi et al 13 reported CDI recurrence in 40% (n = 4) of the DLI group which occurred 1-7 months after surgery. All cases were successfully treated with vancomycin per ostomy or fecal transplant.…”
Section: Discussionmentioning
confidence: 86%
“…One final study was excluded as this particular article reported a reanalysis of the same patients in one of the other included studies. 13 Five studies contributed to the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…23 Loop ileostomy may be a viable surgical alternative to total abdominal colectomy (TAC), but no clear survival benefit was demonstrated to date, 24 and with preservation of the colon recurrence of difficult-to-treat CDI is a concern. 25…”
Section: Fmt For Severe and Fulminant CDImentioning
confidence: 99%
“…23 Loop ileostomy may be a viable surgical alternative to total abdominal colectomy (TAC), but no clear survival benefit was demonstrated to date, 24 and with preservation of the colon recurrence of difficult-to-treat CDI is a concern. 25 Despite improved surgical techniques and predictive models, postsurgical mortality remains high. 23,26 The emergent nature of surgery or delay in surgical intervention after medical failure may contribute to this.…”
Section: Current Guideline Recommendations For Fmtmentioning
confidence: 99%